Right of conscientious objection of the medical staff and abortion : analysis of a legislative proporsal and a judgment from the Constitutional Court of Spain (Prudentia Iuris, 2017)
The purpose of the present work is to analyze the legitimate exercise of the right to conscientious objection in the personal sanitary, when the patient requests the voluntary interruption of pregnancy, delimiting its scope and legally protectable outline within the Spanish legal system, from the Analysis of the preliminary draft formulated to reform the Organic Law Nº 2/2010, of March 3, on sexual and reproductive health and the interruption of pregnancy and the Judgment of the Spanish Constitutional Court, dated September 25, 2014.
Keywords: Conscientious objection; Abortion; Voluntary termination of pregnancy; Registration